Are astrocytes executive cells within the central nervous system? - Sica, Roberto Ernesto Pedro (2016)
Experimental evidence suggests that astrocytes play a crucial role in the physiology of the central nervous system (CNS) by modulating synaptic activity and plasticity. Based on what is currently known we postulate that astrocytes are fundamental, along with neurons, for the information processing that takes place within the CNS. On the other hand, experimental findings and human observations signal that some of the primary degenerative diseases of the CNS, like frontotemporal dementia, Parkinson’s disease, Alzheimer’s dementia, Huntington’s dementia, primary cerebellar ataxias and amyotrophic lateral sclerosis, all of which affect the human species exclusively, may be due to astroglial dysfunction. This hypothesis is supported by observations that demonstrated that the killing of neurons by non-neural cells plays a major role in the pathogenesis of those diseases, at both their onset and their progression. Furthermore, recent findings suggest that astrocytes might be involved in the pathogenesis of some psychiatric disorders as well.